Pengaruh corporate governance dan corporate social responsibility disclosure terhadap nilai Perusahaan dengan pergerakan laba sebagai pemoderasi - Julito, Kiko Armenita; Maimunah, lailatul (Universitas 17 Agustus 1945 Jakarta, 2025)
This research aims to analyze the influence of corporate governance and corporate social responsibility (CSR) disclosure on company value, with profit movements as a moderating variable. Good corporate governance is expected to increase transparency and accountability, thereby influencing CSR disclosure which can increase the company's reputation and value. The research results show that CSR disclosure contributes positively to company value, while profit movements play an important role in strengthening this relationship. This research provides insight into the importance of integration between corporate governance and CSR practices in company strategies to achieve long-term sustainability, This report also uses secondary data obtained from the annual reports of companies listed on the Indonesian Stock Exchange (BEI) for the 2021-2023 period. Data analysis was carried out using Stata software, using a panel data regression approach to test the proposed hypothesis.